2022
DOI: 10.1172/jci.insight.165108
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structure signatures are associated with immune checkpoint inhibitor related acute interstitial nephritis

Abstract: Tertiary lymphoid structures (TLSs) are associated with anti-tumor response following immune checkpoint inhibitor (ICI) therapy, but a commensurate observation of TLS is absent for immune related adverse events (irAEs) i.e. acute interstitial nephritis (AIN). We hypothesized that TLS-associated inflammatory gene signatures are present in AIN and performed NanoString-based gene expression and multiplex 12-chemokine profiling on paired kidney tissue, urine and plasma specimens of 36 participants who developed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Kidney. TLSs can be induced in CKDs, including IgA nephropathy [158][159][160] , lupus nephritis 65 , IgG4-related kidney diseases 161 , interstitial nephritis 162,163 , membranous nephropathy 164 and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis 165,166 as well as in kidney allografts 37,39,44,[167][168][169][170] . Clinical studies have demonstrated that TLS formation is associated with poor kidney outcomes in these diseases (Supplementary Table 2).…”
Section: Chronic Inflammatory Diseases and Ageingmentioning
confidence: 99%
“…Kidney. TLSs can be induced in CKDs, including IgA nephropathy [158][159][160] , lupus nephritis 65 , IgG4-related kidney diseases 161 , interstitial nephritis 162,163 , membranous nephropathy 164 and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis 165,166 as well as in kidney allografts 37,39,44,[167][168][169][170] . Clinical studies have demonstrated that TLS formation is associated with poor kidney outcomes in these diseases (Supplementary Table 2).…”
Section: Chronic Inflammatory Diseases and Ageingmentioning
confidence: 99%
“…As our understanding of irAE mechanisms in patients evolve, it will help to identify which, if any, animal models most accurately recapitulate organ-specific irAEs in patients and inform the next generation of irAE models that can be used to test the relationship between irAE therapeutics and antitumor efficacy. 53 As T cells are thought to be central to the antitumor responses driven by ICIs 4,9 and are found to predominate the immune cell infiltrate in irAE tissue biopsies across organ systems, 8,10,11,13,16,23,38,[54][55][56][57] many studies have looked at the relationship of T cells in irAEs and paired tumors. While central and peripheral tolerance mechanisms cause many autoreactive T cells to become anergic or die during Tcell development, autoreactive T cells are still commonly found in humans 14,44 and are anticipated to play a role in the development of irAEs.…”
Section: The Molecul Ar Rel Ati On S Hip B E T Ween Irae S and Antitu...mentioning
confidence: 99%
“…69 B cells, particularly in the formation of tertiary lymphoid structures, have been found to play a role in antitumor responses 70 as well as irNephritis. 13 The emerging role of B cells in antitumor immunity suggests that interventions to mitigate antibody-mediated irAEs could have negative consequences for tumor immunity.…”
Section: The Molecul Ar Rel Ati On S Hip B E T Ween Irae S and Antitu...mentioning
confidence: 99%
See 2 more Smart Citations